Profil Hasil Belajar Mahasiswa Pendidikan Fisika Dalam Penyusunan Perangkat Pembelajaran - Muhammad Minan Chusni (Alpatih Harapan Semesta, 2023)
The ability to develop learning tools is a fundamental pedagogical competence that prospective physics teachers must possess to ensure effective learning implementation. However, how well Physics Education students perform in developing learning tools remains an important question, particularly in the context of preparing future educators. This study positions learning outcomes in learning tool development as an indicator of students’ readiness to carry out professional teaching practices. The study aimed to describe the learning outcomes profile of Physics Education students in developing learning tools. A quantitative descriptive approach was employed involving 35 Physics Education students. Data were collected through the assessment of four components of learning tools, namely learning activity time allocation, teaching material mapping and attendance planning, syllabus/lesson plan development, and learning assessment. The findings revealed that students achieved high scores in teaching material mapping and attendance planning (89.46), learning activity time allocation (87.40), and syllabus/lesson plan development (82.83). In contrast, learning assessment obtained the lowest score (69.51), indicating challenges in designing appropriate assessment instruments. These findings suggest that students demonstrate good competence in instructional planning but require further support in assessment development. Therefore, learning activities emphasizing authentic assessment design and evaluation practices are recommended to strengthen prospective physics teachers’ pedagogical competence.